Control system adaptation via combined application of point- and interval-based algorithms - Rotach, V. Ya (Automation and remote control, 2011)
Online adaptation of automatic control systems involving point-based algorithms is considered; fixed parameters of the systems are estimated at the start-up stage using interval-based algorithms.